VOCATIONAL SCHOOL ENTREPRENEURSHIP COMPETENCE: DO INTELLECTUAL SKILL, SCHOOL GRADE, AND LEARNING ENVIRONMENT MATTER? - Nafiati, Dewi Amaliah; Sukirno, Sukirno; Saidah, Ati; Rajli, Firstnanda Fattan Al (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
Vocational High Schools (SMK) have an important role in preparing human resources to face the challenges of the world of work. Data in the field shows that unemployment of vocational school graduates continues to increase, so entrepreneurial competence as a solution to overcome unemployment among vocational school graduates must be considered. This research aims to examine the factors that influence entrepreneurial competence in vocational school students, namely intellectual skills, academic values, and learning environment. Data was collected through an online survey involving 250 vocational school students in Central Java Province. The research instrument was adapted from existing economic and entrepreneurship literacy tests. Data were analyzed using the Covariance-Based Structural Equation Modeling (CBSEM) method. The research results found that school rankings had a significant and positive effect on entrepreneurial competence in vocational schools and were related to the learning environment and students' intellectual abilities. This study recommends learning strategies that integrate academic values, intellectual skills, and the learning environment to produce graduates who are ready for the world of work, able to create independent business opportunities, and contribute to the local economy.